2007
DOI: 10.5688/aj710358
|View full text |Cite
|
Sign up to set email alerts
|

Using Interactive Digital Images of Products to Teach Pharmaceutics

Abstract: Objective. To implement interactive digital images of drug products and online quizzes in a pharmaceutics course to teach students where to look on product labels for information and how to evaluate ingredients of various dosage forms, and to reinforce pharmaceutical calculations with practical problems. Design. Interactive digital images of drug products and a database of quiz questions pertaining to the products were created and an interactive online platform was designed. The interactive digital images were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…16 This is the first study to demonstrate significant changes in students' knowledge, attitudes, and skill mastery using this innovative approach to teaching Medicare Part D. Further evaluation is necessary to determine whether these changes are reproducible with real patient encounters by pharmacy students.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…16 This is the first study to demonstrate significant changes in students' knowledge, attitudes, and skill mastery using this innovative approach to teaching Medicare Part D. Further evaluation is necessary to determine whether these changes are reproducible with real patient encounters by pharmacy students.…”
Section: Discussionmentioning
confidence: 89%
“…One study evaluated the use of interactive digital images of prescription labels (as an alternative to passing bottles around the large class) and showed this technique to be an effective and well-received way for first-year pharmacy students to gain exposure to product-labeling in pharmaceutics. 16 Both problem-based and computer-based learning have been viewed as effective ways of teaching pharmacy students about Medicare Part D. 17 However, no studies have systematically evaluated the change from baseline of pharmacy students' knowledge, skill mastery, and attitudes over the duration of a health policy course using these teaching techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Fox et al integrated interactive images of current products to allow students to visually explore the product and the ingredients/labels etc. (Fox et al, 2007 ). Subsequent online quizzes resulted in increased competency in the year that these images were integrated, and the authors concluded that these images allowed the students to visualize the dosage forms covered during the lectures, and the accompanying quizzes encouraged application of the knowledge (Fox et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…New and maturing technologies enable traditional principles of pharmaceutical science to be visualized (Curley et al, 2017a ). Whilst there has been some literature to describe the perspectives of visual teaching on pharmaceutical science learning (Fox et al, 2007 ; Yellepeddi and Roberson, 2016 ), limited research is available surrounding effective teaching strategies in pharmaceutical science education and its wide application within pharmacy practice and pharmacy curricula to date (Curley et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation